What controls the future phytoplankton change over the Yellow and East China Seas under global warming? - Lee, Dong-Geon; Oh, Ji-Hoon; Noh, Kyung Min; Kwon, Eun Young; Kim, Young Ho; Kug, Jong-Seong (Frontiers in Marine Science, 2023)
The Yellow and East China Seas (YECS) are productive continental shelves where essential nutrients for phytoplankton growth are mainly supplied by the intrusion of the Kuroshio Current, riverine inputs, and atmospheric deposition. Surface temperatures in YECS are increasing due to global warming, and are projected to increase further. In this study, future changes in YECS biogeochemical processes were evaluated using Coupled Model Intercomparison Project Phase 6 (CMIP6) Earth System Models. We found a great diversity in predictions of future changes in chlorophyll-a over the YECS region. This diversity was determined to be closely related to the extent of phosphorus (P) limitation for phytoplankton growth. Models simulating positive chlorophyll changes tend to simulate increased Dissolved Inorganic Phosphate (DIP) supplies under future global warming. Our study also demonstrated that the intrusion of the Kuroshio Current into the YECS plays a critical role in future changes in DIP and chlorophyll-a by transporting relatively DIP-rich subsurface water from the Kuroshio Current into the marginal sea.